Effect of adult day care centre attendance on hypertension management - Sentebaleng E. Seitshiro; Omololu S. Aluko; Wilhelm J. Steinberg (South African Family Practice)
Background: Hypertension (HT) silently threatens one in three adults, especially older adults, who struggle with blood pressure (BP) control because of limited health access, poor adherence to medication and failure to make lifestyle changes. This increases their risk for heart disease, kidney failure and dementia. Fortunately, adult day care centres (ADCCs) offer hope. These community facilities provide daytime care, including health support services, social activities and exercise. This study investigated the perceived effect of adult daycare centre attendance on BP control and treatment adherence.